MİDE KANSERLİ HASTALARDA KLİNİKOPATOLOJİK PROGNOSTİK FAKTÖRLER - ERSAN, Yılmaz; ERTÜRK, Süphan; ÇİÇEK, Yusuf and TEMİZ, Muhyittin and DİRİCAN, Ahmet and; soy, Gülen (Cerrahpaşa Medical Journal, 2014)
Background.- Despite recent advances in diagnosis and treatment, gastric carcinoma remains a major cause of death in the world. We evaluated the influence of clinicopathologic variables on 5-year survival rate after gastrectomy. Design.- Clinical characteristics were retrieved from the records of all patients who underwent surgical treatment during 1989-1993. Pathologic characteristics were determined from a detailed review of all available histopathologic slides and reports. Results.- This study is based on an analysis of clinic and pathological features of 409 patients with gastric carcinoma operated on between 1989 and 1993 at Cerrahpaşa Medical Faculty Department of General Surgery. Patients were divided into 4 groups: Curative resection (n=154), palliative resection (n=124), palliative gastrojejunostomy (n=57) or feeding gastrostomy / jejunostomy (n=33), and laparotomy alone (n=41). Five-year survival rate of patients undergoing curative resection, palliative resection and that of patients with non resectable tumor was 58%, 12,5% and 0%, respectively. The relationship between clinicopathologic variables and 5-year survival rate was evaluated by univariate and multivariate analysis. In multivariate analysis with logistic regression of 5-year survival, stage, grade, vascular / lymphatic/ perineural invasion, depth of tumor invasion, levels of metastatic nodes and number of metastatic nodes were statistically significant in cases of curative resection. The only statistically significant independent prognostic factor with long-term survival was levels of metastatic nodes in cases of palliative resection. Conclusion.- This study illustrates that the most important role for clinicians treating patients with gastric carcinoma should be early detection and aggressive surgery for resectable tumors, followed by detailed pathologic examination.